Report of the Conference of Ministers of Agriculture of the Americas 2021 – Twenty-first Regular Meeting of the Inter-American Board of Agriculture - Inter-American Board of Agriculture (IABA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The Conference of Ministers of Agriculture of the Americas 2021 - Twenty-First Regular Meeting of the Inter-American Board of Agriculture (IABA) was held by virtual means, given the international conditions caused by the COVID-19 pandemic, on 1 and September 2, 2021. The Heads of Delegation of the IICA Member States present elected Ms. Tereza Cristina Corrêa da Costa Días, Minister of Agriculture, Livestock and Supply of Brazil as President of the IABA, and Mr. José Abelardo Mai, Minister of Agriculture, Food Security and Business of Belize as rapporteur of the meeting. The ministerial meeting was opened by the President of the Republic of Costa Rica, Mr. Carlos Alvarado. During this meeting, Mr. Manuel Otero was unanimously re-elected as Director General of IICA for the period 2022-2026; The facilities of the Interpretation Center of Tomorrow for Agriculture (CIMAG) were also inaugurated. The Conference of Ministers of Agriculture of the Americas dealt with "Sustainable Agrifood Systems, Engine of Development of the Americas" and was attended by senior officials from the United Nations (UN) and FAO. Likewise, a ministerial dialogue was held on the situation of African swine fever and its possible effects on the member countries of the Institute. The Inter-American Board of Agriculture received the report of the Director General of IICA on its management in the period 2018-2022; witnessed the delivery of awards to the Leaders of Rurality, as well as the signing of the agreement with the Green Climate Fund (FVC); Likewise, he learned about the report “Perspectives for agriculture and rural development in the Americas: a look at Latin America and the Caribbean”; approved the program budget 2022-2023; and approved the new Statutes of the Inter-American Commission on Organic Agriculture (ICOA), among other matters of relevance to the institutional life of the organization.